Global Risks and Collective Action Failures : What Can the International Community Do? - Otker, Inci (IMF Working Papers; Working Paper ;, 2014)
Abstract What do climate change, global financial crises, pandemics, and fragility and conflict have in common? They are all examples of global risks that can cross geographical and generational boundaries and whose mismanagement can reverse gains in development and jeopardize the well-being of generations. Managing risks such as these becomes a global public good, whose benefits also cross boundaries, providing a rationale for collective action facilitated by the international community. Yet, as many public goods, provision of global public goods suffer from collective action failures that undermine international coordination. This paper discusses the obstacles to addresing these global risks effectively, highlighting their implications for the current juncture. It claims that remaining gaps in information, resources, and capacity hamper accumulation and use of knowledge to triger appropriate action, but diverging national interests remain the key impediment to cooperation and effectiveness of global efforts, even when knowledge on the risks and their consequences are well understood. The paper argues that managing global risks requires a cohesive international community that enables its stakeholders to work collectively around common goals by facilitating sharing of knowledge, devoting resources to capacity building, and protecting the vulnerable. When some countries fail to cooperate, the international community can still forge cooperation, including by realigning incentives and demonstrating benefit from incremental steps toward full cooperation.